2014
DOI: 10.1590/s1516-05722014000200012
|View full text |Cite
|
Sign up to set email alerts
|

Tempo de destilação e perfil volátil do óleo essencial de aroeira da praia (Schinus terebinthifolius) em Sergipe

Abstract: RESUMO:Aos frutos e óleos essenciais da aroeira da praia (Schinus terebinthifolius) atribui-se atividade antimicrobiana sobre bactérias gram positivas além de ação anti-inflamatória. O óleo essencial da aroeira é utilizado no tratamento de micoses, sendo a sua atividade antifúngica atribuída à alta concentração de monoterpenos. Este estudo teve como objetivo determinar o melhor rendimento de destilação de óleo essencial de sementes e folhas da aroeira e os componentes químicos do óleo essencial nos diversos pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 11 publications
0
10
0
6
Order By: Relevance
“…Therefore, to minimize the problems caused by organophosphates and pyrethroids, studies have advanced on the search of bioactive molecules that can substitute as well as act in synergism with conventional insecticides. Thus, Schinus terebinthifolius Raddi, from the Anacardiaceae family, popularly known as rose pepper, "aroeira", is a native plant of the Atlantic Forest, and is easily found in the northeastern region of Paraná where it has been utilized in reforestation areas (CESÁRIO;GAGLIANONE, 2013;OLIVEIRA et al, 2014;FERREIRA-FILHO et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, to minimize the problems caused by organophosphates and pyrethroids, studies have advanced on the search of bioactive molecules that can substitute as well as act in synergism with conventional insecticides. Thus, Schinus terebinthifolius Raddi, from the Anacardiaceae family, popularly known as rose pepper, "aroeira", is a native plant of the Atlantic Forest, and is easily found in the northeastern region of Paraná where it has been utilized in reforestation areas (CESÁRIO;GAGLIANONE, 2013;OLIVEIRA et al, 2014;FERREIRA-FILHO et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…obtained αpinene (27.70%) in a culture implemented in the state of Rio de Janeiro, Brazil Oliveira et al (2014). obtained p-mentha-2,4 (8)-diene (35.34%) whileSantos et al (2014) had limonene (67.15%) in the state of Sergipe, Brazil.…”
mentioning
confidence: 96%
“…Low toxicity of the major compounds was observed when using the fumigation method. The higher the molecular weight and the boiling point were, the lower the volatility of the chemical compounds [ 52 , 53 ]. β-caryophyllene, caryophyllene oxide and calamusenone are sesquiterpenes, and present high boiling points [ 54 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The obtained yield of the EO in this study was also higher when compared with other authors, who used the same extraction method. Oliveira et al (2014) obtained a 2.76% yield in red aroeira seeds. Barbosa et al (2007) reported values of 0.44% (leaves) and 4.65% (seeds), when they extracted EO from leaves and seeds of red aroeira in a 3-hour-period.…”
Section: Yield and Physical-chemical Propertiesmentioning
confidence: 93%